Insect pests of sweetpotato in Uganda: farmers' perceptions of their importance and control practices - Okonya, J.; Mwanga, Robert O.M.; Syndikus, K.; Kroschel, Jürgen (Springer, 2014)
Insect pests are among the most important constraints limiting sweetpotato (Ipomoea batatas) production in Africa. However, there is inadequate information about farmers’ knowledge, perceptions and practices in the management of key insect pests. This has hindered development of effective pest management approaches for smallholder farmers. A standard questionnaire was used to interview individual sweetpotato farmers (n = 192) about their perception and management practices regarding insect pests in six major sweetpotato producing districts of Uganda. The majority (93%) of farmers perceived insect pests to be a very serious problem. With the exception of Masindi and Wakiso districts where the sweetpotato butterfly (Acraea acerata) was the number one constraint, sweetpotato weevils (Cylas puncticollis and C. brunneus) were ranked as the most important insect pests. Insecticide use in sweetpotato fields was very low being highest (28–38% of households) in districts where A. acerata infestation is the biggest problem. On average, 65% and 87% of the farmers took no action to control A. acerata and Cylas spp., respectively. Farmers were more conversant with the presence of and damage by A. acerata than of Cylas spp. as they thought that Cylas spp. root damage was brought about by a prolonged dry season. Different levels of field resistance (ability of a variety to tolerate damage) of sweetpotato landraces to A. acerata (eight landraces) and Cylas spp. (six landraces) were reported by farmers in all the six districts. This perceived level of resistance to insect damage by landraces needs to be investigated. To improve farmers’ capabilities for sweetpotato insect pest management, it is crucial to train them in the basic knowledge of insect pest biology and control.